Pengaruh Hormon Androgen terhadap Ekspresi Gen CD52 di Epididimis Mencit (Mus musculus) - Silvani Permatasari; Dwi Ari Pujianto; Astrid Teresa (Jurnal Kesehatan Andalas, 2020)
Androgen has an important role in regulation epididymal sperm maturation  Epididymal sperm maturation is occurs via interactions between sperm and proteins secreted by epididymal genes that are specifically expressed in a region-specific manner. Mice CD52 exhibited expression in all regions in epididymis. However, the regulation of its expression by androgen is needed to be known as a gene candidate that involved in sperm maturation. Objective: This study was aimed to analyze regulation of mice CD52 expression by androgen and a bioinformatics analysis was performed to predict functional domains of CD52. Methods: bioinformatics analysis using Motif Scan. For experiment, mice divided into 5 groups. The groups were control was injected ethanol 0,1 mL/day and others groups were  3, 5, 10, and 15 day used a androgen receptor antagonist, flutamide that dilute in ethanol at a dose of 50 mg/kg/day. And then quantitative real-time RT-PCR was used to analyse expression of CD52 and it’s normalized to Beta actin. Result: CD52 contained a two potential phosphorylation sites for protein kinase C and casein kinase II, N-myristoylation, and N-glycosylation that showed CD52 is secretory protein and predict it’s attached to sperm membrane. Expression of CD52 was decrease about 93% than control. Conclusion: CD52 expression depend on androgen.Keywords:  androgen; epididymis; sperm maturation; expression of CD52